Study of the Features of the Hemodynamic Status of Patients with Type 2 Diabetes Mellitus - Sadikova N.G; Najmutdinova D.K; Urunbayeva D.A; Abdurasulova.Sh.U (Genius Journals, 2023)
We analyzed daily changes in arterial blood pressure in 50 patients of 45 –65 years old with type 2 diabetes combined with essential hypertension. Sistolicdiastolic hypertension was recorded in the patients with combined pathology. In the main portion of patients blood pressure was not enough low in the night (“non-dippers”). “Night-pickers” and “hyper-dippers” were also confidently more frequent.
Keywords: arterial blood pressure indicators; type 2 diabetes; essential hypertension